FACTORS INFLUENCING THE INCOME OF AYAM TALIWANG CULINARY BUSINESSES IN TALIWANG, MATARAM CITY - Ulum, Miftahul; Mukti Ardiansyah , Akhdiyat; Cahayani, Mimi (ShariaBiz International Journal of Economics & Business, 2025)
This study explores the factors influencing income among Ayam Taliwang culinary businesses in Taliwang, Cakranegara, Mataram City. Using an associative research design and census approach, it examines the effects of capital, workforce size, experience, education level, and working hours on business income among 100 entrepreneurs. Data were collected through structured questionnaires and analyzed with multiple linear regression. The study highlights the significant influence of these variables and identifies experience as the most dominant factor. By addressing a culturally specific context, this research contributes to understanding income determinants in the culinary sector and offers insights for enhancing business practices. The findings support targeted strategies for entrepreneurs and policymakers to foster economic growth in local culinary industries.